A systematic review of the evidence base for vidian neurectomy in managing rhinitis. (4th August 2016) - Marshak, T; Yun, W K; Hazout, C; Sacks, R; Harvey, R J
Abstract: Background: Vidian neurectomy has been proposed as a surgical option for rhinitis refractory to medical treatment. However, the evidence base for its benefit remains controversial. Methods: A systematic review was performed. Studies reporting original data on patients with rhinitis treated by vidian neurectomy were included. Patient-reported outcome measures were the primary outcome investigated; specific peri-operative morbidities were the secondary outcome. Results: A total of 1012 articles fulfilled the search criteria, 32 of which were included in the study. Patient-reported outcome measures were compared before and after surgery in eight studies. There were 529 patients represented in these trials. Significant improvement in rhinorrhoea was reported in all eight studies. Temporary dry eyes was reported in 24.63 per cent of cases (272 out of 1104 cases). There was no report of cranial nerve deficit or eye movement disturbance. Conclusion: Endoscopic vidian neurectomy does have a role in the surgical management of refractory rhinitis, particularly in patients with non-allergic rhinitis, but a well-designed cohort trial would be advantageous to clarify long-term outcomes.